Marketing Models And Strategies For Frozen Food-Based Agricultural Products In The New Normal Era - Megawati; Wahyuni Zam; Budiman Haruna; Nur Alam Kasim; Mukhlis Mukhlis (Cita konsultindo, 2024)
The marketing of frozen food products from agriculture / fisheries is very good with the increase in world per capita product consumption every year and the need for people to live healthy, hygienic and practical lives is getting higher. However, since COVID-19 became a world pandemic, consumer behavior towards the consumption of frozen food products such as frozen fish, frozen meat, frozen vegetables and processed frozen agricultural/fishery products has changed both regarding channels and marketing mix in facing the new normal era. This study aims to identify models and strategies carried out by frozen food-based agricultural product business actors in marketing their products in the new normal era. Determination of regional samples (Makassar, Maros and Gowa districts) and respondents purposively. The number of samples used in this study was 20% of the total frozen food-based agricultural product business actors. The analysis methods used are: qualitative descriptive analysis. The results showed that the marketing of frozen food-based agricultural products business applies the ice cream business model with the application of 5 (five) marketing strategies so that the business can survive in the new normal era. This study suggests that policies from the government that are fast and responsive can help provide business capital assistance to anticipate the potential bankruptcy of frozen food-based agricultural product businesses.